Ongoing Pregnancies following Cosmetic Micromanipulation of Preimplantation Embryos in Patients with Implantation Failure - Iman Halvaei; Mohammad Ali Khalili; Somayyeh Safari; Navid Esfandiari (Case Reports in Medicine)
Cosmetic micromanipulation is defined as fragment and coarse granulation removal from preimplantation embryos. We report two cases of pregnancies in patients with implantation failure following cosmetic micromanipulation.